Sociodemographic strata and patterns related to the first union and first motherhood in Mexico, 2018 - Ortíz-Ávila, Elsa (2020)
Introduction: The first union and the first motherhood are key events that start the women's transition to adulthood, so that the aim of this paper is investigating the family formation´s patterns in Mexico, specifically in the first union and the first maternity of two women´s generations, analyzing quantum and tempo according to the sociodemographic stratum. Methodology: This study analyzes the National Survey of Demographic Dynamics of 2018. Initially, the two events’ quantum and tempo are studied by the survival analysis. Finally, to determine if the sociodemographic stratum is associated with the occurrence of the calendar of events, two Cox proportional hazards models are adjusted. Results: It can be observed that women born between 1984 and 1988, located among the lowest sociodemographic strata have the same demographic behaviors as those women of the same stratum who were born twenty years earlier. It is important to see that those women who belong to the highest strata have postponed the entry of these two events, so important from the social and cultural perspective of Mexico. Conclusions: The demographic behavior’s patterns related to family formation in Mexico ratify that this is a country with very established cultural, social and family behavior standards, that even in the younger generations these patterns continue to be transmitted. Therefore, it is very important to continue analyzing the tempo and the quantum of the first union and the first motherhood.